Synopsis of extinct Bruchomyiinae (Diptera, Psychodidae) from Burmese, Baltic and Dominican amber, with descriptions of new genera and species - Wagner, Rüdiger (Zootaxa, 2017)
Bruchomyiinae from Burmese, Baltic, and Caribbean amber are revised. Five new species from Baltic, one from Caribbean and three from Burmese amber are described. Based on recently discovered specimens, additional details and corrections for previously described species are provided. Six species from Baltic amber were combined in Hoffeinsodes gen. nov. (Hoffeinsodes obtusa sp. nov., H. bifida sp. nov., H. cubicula sp. nov., H. longicauda sp. nov., H. reducta sp. nov. and H. hoffeinsi (Wagner 2006) comb. nov.), based on the fusion of gonocoxites and hypandrium, and a laterally expanded epandrium with posterolateral lobes. Genus Palaeosycorax Meunier, 1905 is re-validated, with Palaeosycorax inexpetatus (Wagner, 2012) comb. nov. included. Caribbean amber species Boreofairchildia dominicana sp. nov. and B. hennigianus (Schlüter, 1978) comb. nov. are congeneric with extant genus Boreofairchildia Wagner & Stuckenberg, 2016. Three new and two described species from Burmese amber are combined in Palaeoglaesum gen. nov. (Palaeoglaesum quadrispiculatum (Stebner et al., 2015) comb. nov., P. velteni (Wagner, 2012) comb. nov., P. muelleri sp. nov., P. bisulcum sp. nov., P. notandum sp. nov.), based on their small size relative to other Bruchomyiinae, and presence of a Y-shaped aedeagal sclerite. Keys to males of species in particular ambers are provided.